Formation mechanism of the steel/nickel heterogeneous metal interwoven by the arc additive manufacturing process - Benshun ZHANG; Zheng ZHANG; Hongwei SUN; Yugang MIAO; Yuyang ZHAO; Yu LIU (Hanjie xuebao)
To enhance the overall forming strength of steel/nickel tubular structures (Ni-clad inner wall and steel-shell outer wall), this study employed double-wire arc additive manufacturing technology and proposed an outward-inward and bottom-up double-wire interwoven path strategy. The deposition temperature field was monitored using infrared thermal imaging, while electron backscatter diffraction (EBSD) was applied to analyze the interface of metallographic specimens. Results showed defect-free formation with no apparent cracks or deformations in the integrated structure. Both inner and outer layers exhibited minimal temperature variations during deposition, showing negligible impact on geometric forming accuracy. The steel-nickel interface presented an interwoven morphology with non-preferentially oriented grains on both sides, existing as a mutual solid solution. Localized stress concentration was observed at the interwoven interface, where grains maintained stable configurations without significant recrystallization. This proposed interwoven path strategy achieves Fe/Ni interface solid solution strengthening and mechanical interlocking, providing a novel approach for high-performance additive manufacturing of dissimilar metal structures.